How Does Zinc Improve Salinity Tolerance? Mechanisms and Future Prospects - Jinhua Shao; Wei Tang; Kai Huang; Can Ding; Haocheng Wang; Wenlong Zhang; Ronghui Li; Muhammad Aamer; Muhammad Umair Hassan; Rehab O. Elnour; Mohamed Hashem; Guoqin Huang; et al. (Plants, 2023)
Salinity stress (SS) is a serious abiotic stress and a major constraint to agricultural productivity across the globe. High SS negatively affects plant growth and yield by altering soil physio-chemical properties and plant physiological, biochemical, and molecular processes. The application of micronutrients is considered an important practice to mitigate the adverse effects of SS. Zinc (Zn) is an important nutrient that plays an imperative role in plant growth, and it could also help alleviate the effects of salt stress. Zn application improves seed germination, seedling growth, water uptake, plant water relations, nutrient uptake, and nutrient homeostasis, therefore improving plant performance and saline conditions. Zn application also protects the photosynthetic apparatus from salinity-induced oxidative stress and improves stomata movement, chlorophyll synthesis, carbon fixation, and osmolytes and hormone accumulation. Moreover, Zn application also increases the synthesis of secondary metabolites and the expression of stress responsive genes and stimulates antioxidant activities to counter the toxic effects of salt stress. Therefore, to better understand the role of Zn in plants under SS, we have discussed the various mechanisms by which Zn induces salinity tolerance in plants. We have also identified diverse research gaps that must be filled in future research programs. The present review article will fill the knowledge gaps on the role of Zn in mitigating salinity stress. This review will also help readers to learn more about the role of Zn and will provide new suggestions on how this knowledge can be used to develop salt tolerance in plants by using Zn.